Activity competence among infants and toddlers with developmental disabilities: Rasch analysis of the Infant Toddler Activity Card Sort (ITACS) - Catherine R. Hoyt; Allison J. L'Hotta; Anna H. Bauer; Chih-Hung Chang; Taniya E. Varughese; Regina A. Abel; Allison A. King (SpringerOpen, 2021)
Abstract Background Development is rapid in the first years of life. Developmental delays appearing during this critical period have the potential to persist throughout the child's life. Available standardized assessments for this age record a child's ability to successfully complete discrete skills but fail to capture whether the child incorporates those skills into daily routines that are meaningful to the child and family. The Infant Toddler Activity Card Sort (ITACS) is a newly developed photograph-based early intervention tool to measure the participation-related concept of activity competence using caregiver report. The purpose of the present study was to use Rasch analysis to determine if ITACS items comprehensively measure the construct of child activity competence. Results A total of 60 child/caregiver dyads participated. The dichotomous caregiver-reported responses (present vs. absent) on the 40 individual ITACS items were used in Rasch analysis, and three iterations of the model were completed. The final model included 51 child/caregiver dyads and 67 ITACS assessments with a good spread of individual ability measure (6.47 logits). All items demonstrated adequate infit except for "sleeping" (range 0.68-1.54). Five items (sleeping, eating at restaurants, brushing teeth, crawling, and interact with pets) demonstrated high Mean Square (MNSQ) outfit statistics and one (take a bath) demonstrated low MNSQ outfit. ITACS items demonstrated a good spread of item difficulty measures (6.27 logits), and a clear ceiling was observed. Three activity items (smiling, breastfeeding, and playing with adults) were rarely endorsed as concerns. The activities most likely to be reported as challenging were "crying/communicating" and "going to school". Person and item reliability statistics were adequate (0.79 and 0.80, respectively). The separation between individuals and between items were adequate to good (1.96 and 1.99, respectively). Conclusions Findings indicate that ITACS items are measuring a unidimensional construct--activity competence in early childhood. The Rasch analysis of caregiver responses suggest that some activities are more likely to be considered challenging and may be important targets for intervention. These results provide evidence to further validate the ITACS as a caregiver report measure and support its use in the early intervention setting to facilitate caregiver driven goal development.